The sanctuary of Bethel and the configuration of Israelite identity - Gomes, Jules Francis (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2006)
After Jerusalem, Bethel is the most frequently cited sanctuary in the Hebrew Bible. The book offers a detailed analysis of Bethel and its sanctuary from archaeological and biblical evidence. It reconstructs the history of Bethel and by analysing the presence of pro- and anti-Bethel propaganda, it argues that the latter, with its own pro-Jerusalem/Judah bias, has resulted in an unfair denigration of Bethel as an idolatrous place of worship. The study suggests that Bethel was a legitimate Yahwistic shrine and continued to be so even after the fall of the Northern Kingdom of Israel to the Assyrians. Hence, Bethel in a real sense was the principal means of configuring Israelite identity.